Divergent gold-catalysed reactions of cyclopropenylmethyl sulfonamides with tethered heteroaromatics - Drew, Melanie A.; Arndt, Sebastian; Richardson, Christopher; Rudolph, Matthias; Hashmi, A. Stephen K.; Hyland, Christopher J. T. (Chemical communications, 2019)
Cyclopropenylmethyl sulfonamides with tethered heteroaromatics have been demonstrated to undergo divergent gold-catalysed cyclisation reactions. A formal dearomative (4+3) cycloaddition takes place with furan-tethered substrates, yielding densely functionalised 5,7-fused heterocycles related to the bioactive curcusone natural products. Indole-tethered substrates display divergent reactivity giving biologically important tetrahydro-β-carbolines via a Friedel-Crafts mechanism.
Gesehen am 10.01.2020